Amerika Serikat sebagai Negara Adikuasa: Pengaruh dan Dominasi dari Akhir Abad ke-20 hingga Awal Abad ke-21 - Nuridah, Ilah; Aulia, Thoriq; Sahada, Nanda Aulia; Rodiyah, Zahrotun; Ndruru, Sitevis; Simangunsong, Winda; Rila, Eka Salva; Tampubolon, Yosafat Lesmana (Medan Resource Center, 2024)
This research analyzes the role and influence of the United States as a superpower from the late 20th century to the early 21st century, focusing on military, economic, political, and cultural power. After the Soviet Union's collapse, the United States became the dominant force in international policy, with significant global power projection through a large defense budget and advanced technology. Economically, its influence is seen in the dollar's dominance and leading technology companies. Politically, the U.S. plays a central role in international organizations like the UN and NATO. Culturally, American media and technology have led to widespread